RESTORATIVE EFFECT OF BETULA ALNOIDES BARK ON HEPATIC METABOLISM IN HIGH FAT DIET FED WISTAR RATS - DOMINIC AMAL RAJ,; MALARVILI. T,; VELAVAN. S, (International Journal of Pharma and Bio Sciences, 2015)
Liver has been shown to play a central role in the maintenance of lipids and glucose homeostasis. The objective of this study was to evaluate regulatory effect of Betula alnoides bark extract (BABE) in a rat model of high fat diet (HFD)-induced obesity. The carbohydrate metabolic enzymes Glycogen phosphorylase, Hexokinase, Fru, 1,6-bis-phosphatase, Phosphoglucose isomerase, Glu-6-phosphatase, Glucose-6-phosphate dehydrogenase and the content of pyruvate and glycogen were measured in experimental rats. The lipid metabolic enzymes HMG co A reductase, Total lipase, lecithin cholesterol acyl transferase (LCAT) and lipoprotein lipase (LPL) were measured in experimental rats. Supplementation of BABE to obesity rats for 8 weeks restored the altered carbohydrate and lipid metabolizing enzymes. The results of the present study indicate that BABE supplementation could be helpful in overcoming the deregulations of glucose and lipid metabolism in high fat fed rats.